Signatures of positive selection for local adaptation of African native cattle populations: A review - Wondossen AYALEW; Xiao-yun WU; Getinet Mekuriaw TAREKEGN; Min CHU; Chun-nian LIANG; Tesfaye SISAY TESSEMA; Ping YAN (Journal of Integrative Agriculture)
Cattle are central to the lives and diverse cultures of African people. It has played a crucial role in providing valuable protein for billions of households and sources of income and employment for producers and other actors in the livestock value chains. The long-term natural selection of African cattle typically signals signatures in the genome, contributes to high genetic differentiations across breeds. This has enabled them to develop unique adaptive traits to cope with inadequate feed supply, high temperatures, high internal and external parasites, and diseases. However, these unique cattle genetic resources are threatened by indiscriminate cross-breeding, breed replacements with exotic cosmopolitan breeds, and climate change pressures. Although there are no functional genomics studies, recent advancements in genotyping and sequencing technologies have identified and annotated limited functional genes and causal variants associated with unique adaptive and economical traits of African cattle populations. These genome-wide variants serve as candidates for breed improvement and support conservation efforts for endangered cattle breeds against future climate changes. Therefore, this review plans to collate comprehensive information on the identified selection footprints to support genomic studies in African cattle to confirm the validity of the results and provide a framework for further genetic association and QTL fine mapping studies.